2019
DOI: 10.1159/000495151
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNAs in Thyroid Cancer: Implications for Pathogenesis, Diagnosis, and Therapy

Abstract: Thyroid cancer is a rare malignancy and accounts for less than 1% of malignant neoplasms in humans; however, it is the most common cancer of the endocrine system and responsible for most deaths from endocrine cancer. Long non-coding (Lnc)RNAs are defined as non-coding transcripts that are more than 200 nucleotides in length. Their expression deregulation plays an important role in the progress of cancer. These molecules are involved in physiologic cellular processes, genomic imprinting, inactivation of chromos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 72 publications
1
50
0
Order By: Relevance
“…At present, the speci city of GBC diagnosis is relatively low, and patients with advanced stage have poor progression and high mortality. It is well documented that lncRNAs and miRNAs are potential therapeutic targets for various cancers [23]. Herein, we aimed to explore regulatory mechanism between UCA1 and miR-613 in GBC.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the speci city of GBC diagnosis is relatively low, and patients with advanced stage have poor progression and high mortality. It is well documented that lncRNAs and miRNAs are potential therapeutic targets for various cancers [23]. Herein, we aimed to explore regulatory mechanism between UCA1 and miR-613 in GBC.…”
Section: Discussionmentioning
confidence: 99%
“…It is commonly observed that alteration of lncRNAs occurred in thyroid cancer [31]. A series of lncRNAs have been found to play oncogenic or suppressor roles in thyroid cancer, of which some are suggested as potential therapeutic targets [31][32][33][34]. To our knowledge, it is the rst time that the differential lncRNAs have been screened out among NTs, PTCs and DDTCs from the FUSCC cohort to identify a lncRNA biomarker associated with dedifferentiation of thyroid cancer, which was speci cally altered in ATC, and then was con rmed to regulate the malignancy of ATC.…”
Section: Discussionmentioning
confidence: 99%
“…Long noncoding RNAs (lncRNAs) refer to the type of noncoding RNA that is derived from genome-encoded transcripts with lengths longer than 200 RNA nucleotides (3). Recent studies suggest it may be directly involved in the regulation of development of tumor cells (4)(5)(6).…”
Section: Introductionmentioning
confidence: 99%